(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Although death is an everyday occurrence in the critical care units, there is a discomfort in confronting mortality in 21st century society. Advance life support interventions have greatly improved the prospects of treating seriously ill patients, but at the same time futile prolonged life support interventions can make death painful and agonising. There is absence of guidelines in India regarding end of life issues especially with regards to withholding/ withdrawing advance life support. Further, euthanasia, living will, do not resuscitate (DNR) and advance directives are not legally acceptable in the court of law. All this has created a dilemma for the doctors/patients and their relatives. Laws regarding harvesting of organs from brain dead patients are also not clearly defined. Revision of the primitive laws and introduction of new legislation on the lines of improve the western model will improve the of end of life decision making in India. Introduction of end of life issues in medical curriculum and training of physicians in ethical decision making, advance directives and counselling in the intensive care units, will improve the dismal Indian scenario.